HEALTH-RESTORING SMART BAG FOR MEDICAL WORKERS: AN EMOTIONAL AND PHYSICAL RECOVERY SYSTEM (Eureka Journal of Health Sciences & Medical Innovation, 2026)
It is known that medical employees, especially doctors and nurses, have high responsibility, an intensive work mode, and emergencies because of continuous psycho-emotional stress under the circumstances. They are often faced with medical bags and work equipment, mainly functional items, for transportation and to keep for intended stress reduction or emotional recovery provision to the function owner.Therefore, work on the process stress level of employees to reduce the directed integrated technical solution does not.